(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Due to the educational transformation from traditional to digital learning in Jordan, caused by the COVID-19 pandemic, the purpose of this study was to contribute to this transformation in design education. Considering the practical nature of graphic and interior design education, this study aims to evaluate the usability of the Moodle-Learning Management System based on design students’ assessments. It also aims to explore design students’ preferences for learning environments; (Traditional, Online, Blended) based on course types in design programs (non-design courses, theoretical design courses, and practical/ studio-based courses). A quantitative approach was employed using a designed questionnaire developed from the Shackel usability model (1991) to conduct the research study. A total of (218) undergraduate graphic and interior design students from the design department at Yarmouk University participated in this study, and all the questionnaires were collected and analyzed in SPSS. The findings of this study have indicated that both the practical nature of design education and the late adoption of digital learning affect the usability evaluation of LMS and design students’ preferences for the learning environment. It was concluded that there is a need for implementing new pedagogies to enhance design students’ experience, satisfaction, and acceptance of digital learning.